Genetic polymorphisms of methylenetetrahydrofolate reductase (MTHFR) gene and susceptibility to depression in Asian population: a systematic meta-analysis - Rai, V. (Cellular and Molecular Biology, 2014)
Genetic association studies on MTHFR C677 T polymorphism and depression have been repeatedly performed over the last two decades and results are generally inconsistent. The aim of the present study was to assess the risk of MTHFR C677T polymorphism for depression in Asian population. The author performed a meta-analysis and pooled data from individual case-control studies that examined the association between C677T polymorphism and depression (meta-analysis: 13 studies, 1,120 cases and 1,688 controls).The pooled Odd Ratios (OR) were estimated by both fixed effects and random effects models. Overall, there was an association between MTHFR C677T polymorphism and increased risk of depression under five genetic models (OR T vs. C=1.44, 95% CI= 1.56-1.78, P=0.001; OR TT vs. CC= 1.78, 95% CI 1.17– 2.69, P=0.006; OR CT vs CC=1.102, 95% CI=0.91-1.32,P=0.31; OR TT vs. CT+CC=1.73, 95% CI= 0.87-3.41, P=0.11; OR TT+CT vs. CC=1.26, 95% CI=0.96-1.64, P=0.08). Sensitivity analysis suggested exclusion of any single study did not alter the overall pooled Ors. In conclusion results of present meta-analysis supports that there is a significant association between MTHFR C677T polymorphism and depression risk, and MTHFR 677T allele contributes to increased risk of depression in Asian individuals.